ADAPTASI BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L.) PADA DATARAN RENDAH DENGAN PEMBERIAN PUPUK KANDANG DAN NPK - Ahmad Andri Kusuma; E. Harso Kardhinata; Mbue Kata Bangun (Universitas Sumatera Utara, 2013)
The adaptation of some shallot varieties has been conducted with the application of chicken manure andNPK fertilizer. The goal of this research is to know the adaptation of some shallot varieties in lowlandapplication of chicken manure and NPK fertilizer. The research was conducted at community land onPasar 1 Medan Selayang, Medan with altitude of 25 meters above sea level from May to July 2012. Usingrandomized block design. The first factor is three shallot varieties are Kuning, Medan, and Maja. Thesecond factor is four types of fertilizer; control, 240 g/plot chicken manure, 48 g/plot NPK, and chickenmanure plus NPK. The results showed that the varieties and fertilizer are significant in the fresh weightand number of cloves but not significant in plant height, number of tillers per hill, and dry weight. Whereas the interaction between varieties with fertilizers are not significant in all parameters. Heritability valuesranged from 0.03 - 0.87. All of the varieties tested have not been able to adapt well in the lowland interms of production so further studies using different varieties in the lowland is suggested.Key Words : shallot varieties, low land, chicken manure, NPK fertilizer.